Translating basic research in cancer patient care - Marcello Maugeri-Saccà; Ruggero De Maria (Istituto Superiore di Sanità, 2011)
With the advent of molecular targeted therapies and the development of high-throughput biotechnologies, it has become evident that progress in cancer research is largely due to the creation of multidisciplinary teams able to plan clinical trials supported by appropriate molecular hypotheses. These efforts have culminated in the identification and validation of biomarkers predictive of response, as well as in the generation of more accurate prognostic tools. The identification of cancer stem cells has provided further insights into mechanisms of cancer, and many studies have tried to translate this biological notion into prognostic and predictive information. In this regard, new agents targeting key stemness-related pathways have entered the clinical development, and preliminary data suggested an encouraging antitumor activity.